Is the household sector over-indebted in China? – the perspective of economic growth and financial risks - Liu, Ziwei; Zheng, Xuemei; Zou, Fenju (Technological and Economic Development of Economy, 2025)
In this paper, we introduce household debt into a general equilibrium model and investigate the sources of changes in household debt through the lens of leverage constraints of the household sector, firms, and banks. Based on this, we analyze the impacts of household debt on economic growth and the financial risks embedded in debt-stimulated economic growth. After fitting our model to the data from China, we find that the increase in household debt in China is conducive to economic growth as it promotes demand growth and reduces financial frictions. In addition, the marginal financial risk induced by the growth of household debt is relatively small, implying that the increase in household debt can some- what promote economic growth without accumulating much endogenous vulnerability in the economy. This contrasts with the reduction of firms’ debt, which leads to drastic negative economic fluctuations in the short term, although it is beneficial to economic growth in the long run given that firms have already been caught in a vicious debt-deflation cycle. Therefore, to ensure the stability of the economy in China, it is plausible to squeeze out firms’ debt through increasing debt in the household sector. First published online 12 February 2025